Depiction of Masculinity in the Advertisement 'PRUFuture Prudential Life Insurance, #SimpleButMeaningful Protecting Families Now and in the Future' - Diza Aulia Herdani; Hendri Prasetya; Titin Setiawati (Hasanuddin University, 2025)
Traditional masculinity remained deeply embedded in society, associating values such as strength, independence, power, and work primarily with men. This study aimed to examine the portrayal of masculinity in the male lead character of Prudential Indonesia’s advertisement titled